1999
DOI: 10.1080/105172399242591
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Purified Ms2 Bacteriophage by the Physical Counting Methodology Used in the Integrated Virus Detection System (Ivds)

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 0 publications
3
24
0
Order By: Relevance
“…The samples were dialyzed against 25 mM ammonium acetate at acidic (2.8) and neutral (7.4) pH. MS2 was purified as previously described [18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were dialyzed against 25 mM ammonium acetate at acidic (2.8) and neutral (7.4) pH. MS2 was purified as previously described [18].…”
Section: Methodsmentioning
confidence: 99%
“…A recent study successfully compared the diameter of 32 monomeric and multimeric globular proteins based on their ion mobility [17] and demonstrated the potential of IMS for studying intact virus particles. A second IMS study reported that the modal diameter of MS2 particles could be measured using IMS [18].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in the previous section, the first reported application of ES-DMA to biological molecules was by Kaufman et al in 1996 for characterizing proteins. This work was followed over the next decade by several reports from Allmaier et al [11], Wick et al [12] and de la Mora et al [13] related to characterization of several other proteins, viruses and polymers. Starting in 2006 as seen in Figures 1.3A and 1.3B a dramatic increase in the number of publications and citations related to ES-DMA occurred with contributions from Biswas et al [14], Zachariah et al [15], Loo et al [16], Hogan et al [17], Pergantis et al [18], Pease et al [19] and Hackley et al [20].…”
Section: Growth Of Es-dmamentioning
confidence: 98%
“…ET AL. particles have been studied as a means of developing a calibration curve for estimating the molecular masses of large organic complexes (Bacher et al 2001) and to develop an integrated virus detection system (IVDS) for estimating virus particle concentrations and virus particle agglomeration in liquid systems (Wick and McCubbin 1999a). While virus capsid agglomeration has been documented in several studies (Thomas et al 1998;Wick and McCubbin 1999a), previous studies of airborne virus particles have employed the use of electrospray to allow for only single-virus particle aerosolization (Bacher et al 2001;Wick and McCubbin 1999a). Because of their small size, virus particles have a high deposition efficiency within the alveoli of mammalian respiratory systems and can lead to a variety of medical illnesses.…”
Section: Introductionmentioning
confidence: 99%